Економічні важелі впливу на діяльність підприємств: етимологічний, семантичний та типологічний аспекти - Дідик, А. М. (Видавництво Львівської політехніки, 2014)
Розглянуто трактування категорії “економічний важіль” в енциклопедичній, тлумачній та науковій літературі, на підставі чого уточнено її сутність у контексті інструментів економічного характеру, які забезпечують зміну параметрів функціонування підприємства. Виокремлено характерні ознаки економічних важелів, які пов’язані із їх дієвістю, забезпеченням змін, стимулювальним чи стримувальним характером. На підставі аналізування літературних джерел за проблемою розроблено типологію економічних важелів за низкою істотних та незалежних ознак, а саме: за змістом (фіскальні, монетарні, тарифно-цінові, інвестиційні, кредитні, амортизаційні), за цілеспрямованістю використання (цільові, іманентні), за характером впливу (важелі безпосереднього впливу, важелі опосередкованого впливу), за середовищем формування (важелі, що впливають на діяльність підприємства із зовнішнього середовища, важелі, що впливають на діяльність підприємства із внутрішнього середовища функціонування), напрямом впливу (стимулювальні важелі, гальмівні важелі), за рівнем формування (важелі, макроекономічного рівня, важелі мезоекономічного рівня, важелі мікроекономічного рівня), за силою впливу (важелі сильного впливу, важелі середнього впливу, важелі слабкого впливу), за охопленням впливом (комплексні важелі, локальні важелі), за проявом результативності дії важелів (важелі, дія яких проявляється у довгостроковому періоді, важелі, дія яких проявляється у середньостроковому періоді, важелі, дія яких проявляється у короткостроковому періоді), за сферою впливу (важелі здатні діяти на підприємстві на виробничу, збутову, логістичну, фінансово-економічну, технологічно-конструкторську сферу тощо). За результатами досліджень конкретизовано цільове призначення економічних важелів у забезпеченні розвитку підприємств. In the article interpretation of category is considered "economic instrument" in encyclopedic, explanatory and scientific literature, on the basis of what her essence is specified in the context of instruments of economic character, that provide the change of parameters of enterprise functioning. The characteristic signs of economic instruments, that is related to their effectiveness, providing of changes, are distinguished, motivation or by retentive character. On the basis of literary sources analysis for the problem by typology of economic instruments is worked out after the row of substantial and independent signs, namely: on maintenance, after purposefulness of the use (having a special purpose, immanent), by the nature of influence (levers of direct influence, levers of the mediated influence), after the environment of forming (levers, that influence on activity of enterprise froman environment, levers, that influence on activity of enterprise fromthe internal environment of functioning), after direction of influence (motivation levers, brake levers), after the level of forming (levers of macroeconomic level, levers of mezoeconomic level, levers of microeconomic level), after force of influence (levers of strong influence, levers of middle influence, levers of weak influence), after a scope influence (complex levers, local levers), after the display of effectiveness of action of levers (levers the action of that shows up in a long-term period, levers the action of that shows up in a medium-term period, levers the action of that shows up in a short-term period), after the sphere of influence (levers are able to operate on an enterprise on a productive, sale, logistic, finance-economic, technologically-designer sphere and others like that). On the basis of the executed researches the key whole uses of economic instruments of influence are specified on enterprises on a macrolevel, it is reckoned to that: providing of intensive, progressive development of enterprise; a leadingout of enterprise is from the crisis state; introduction and development are on the enterprise of innovations; bringing in of outsourcing of financing; expansion of market share; providing of economy of resources; providing of the having a special purpose use of resources of enterprise; conditioning is for development of skilled and technological potential; providing of economic and financial stability of functioning of enterprises; increase of financial effectiveness of functioning; improvement of financial discipline and solvency; providing of increase of business activity of enterprise; activation of organizational changes of technological, social, administrative character; increase of market value of enterprise; an increase of competitiveness of enterprise is at the market; warning of bankruptcy; realization of sanation events; forming of economicsecurity; activation of foreign economic activity; optimization of charges and others like that. Also outlined aims of economic instruments of influence on enterprises on a macrolevel and a mezolevel of national economy.
Economic instruments of influence on activity of enterprises: etymologic, semantic and typology aspects
Keywords: економічний важіль; інструмент; типологія економічних важелів; вплив; перетворення; economic instrument; instrument; typology of economic instruments; influence; transformation